PEMBENTUKAN KARAKTER ANAK MENURUT ABDULLAH NASHIH ULWAN - Muhammad Hambal (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
The purpose of this study is to discuss the urgency of Islamic education for children and how the theory of character formation of children according to Abdullah Nashih Ulwan. This research is a qualitative study with the type of library research (library research), and the data analysis technique uses inductive and deductive. The findings of this study can be concluded: first, Islamic education is education oriented to the five pillars of religion, namely faith, etiquette, morals, worship, and muamalat. Two pillars are closely related to the afterlife, namely faith and worship. While the other three pillars are related to world affairs, namely morals, manners and muamalat. If you accept the pillars as intended in education, this education will give birth to people who have strong faith, truly worship, both moral and ethical, and are able to involve the community and be involved in life in accordance with the skills (expertise) they have. Second, the theory of the formation of children's characters in accordance with Ulwan began since the creation, and the formation of children's characters to become a being insan kamil (perfect human being) is not enough just to reform the morals, but must discuss some aspects of coaching, good faith education, religious education, moral education, scientific education, and physical education. Because humans are not only like walking objects, but humans consist of spirits and bodies. The morality that is seen is the fruit of the faith and spirituality that is in the soul and feelings. Likewise man was created not to live alone, but he is a social creature that lives and bermuamalah with others.